Utilization of Buildings’ Foundations for a Seasonal Thermal Energy Storage Medium to Meet Space and Water Heat Demands - Ammar Alkhalidi; Hamzah Al Khatba; Mohamad K. Khawaja (International Journal of Photoenergy)
Seasonal thermal energy storage (STES) can be utilized to cover a portion or meet the whole space and water heat demands in residential and commercial buildings. With the scarcity of fuel resources, scientists have become aware of the importance of the utilization of thermal energy. An STES system can be charged using solar collectors to heat a storage medium when solar radiation is available. Solar irradiance is seasonal so this type of system can compensate for the shortage of energy in the winter by storing surplus solar energy in the summer. This study offers an innovative design of an STES system that takes advantage of the backfill space in a building’s underground foundation to install the thermal storage medium on the excavated surface among the support pillars’ base. To study the feasibility and the feasibility of such STES system, the design was simulated using the TRNSYS® tool where the STES medium was charged by a solar thermal system. The chosen building type was a four-story hotel located in three cities each with its unique climate: Potsdam (Germany), Zarqa (Jordan), and Doha (Qatar). The results showed the coverage rate of the building’s annual heat demand was 56%, 82%, and 84%, and the payback periods were 3.4, 4.4, and 29 years for Potsdam, Zarqa, and Doha, respectively. Zarqa is the most efficient and feasible for STES compared to the other two cities.